2020
DOI: 10.21037/atm.2020.02.07
|View full text |Cite
|
Sign up to set email alerts
|

Apelin/Elabela-APJ: a novel therapeutic target in the cardiovascular system

Abstract: Apelin and Elabela (ELA) are endogenous ligands of angiotensin domain type 1 receptorassociated proteins (APJ). Apelin/ELA-APJ signal is widely distributed in the cardiovascular system of fetuse and adult. The signal is involved in the development of the fetal heart and blood vessels and regulating vascular tension in adults. This review described the effects of apelin/ELA-APJ on fetal (vasculogenesis and angiogenesis) and adult cardiovascular function [vascular smooth muscle cell (VSMC) proliferation, vasodil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 103 publications
(127 reference statements)
1
61
0
3
Order By: Relevance
“…Apart from the putative receptor protein related to the angiotensin receptor AT1 endogenous ligand (Apelin), ELA has been regarded as the second endogenous ligand for a kind of orphaned G protein-coupled receptor called APJ (Apelin receptor, APLNR) [ 23 ]. The ELA/APJ system is relevant to multiple biological functions, such as mesodermal differentiation, cardiogenesis, and treatment targets for heart diseases [ 24 – 26 ]. Ho et al discovered that ELA protected human embryonic stem cells against cellular stress and enhanced their self-renewal ability through PI3K/AKT pathway [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the putative receptor protein related to the angiotensin receptor AT1 endogenous ligand (Apelin), ELA has been regarded as the second endogenous ligand for a kind of orphaned G protein-coupled receptor called APJ (Apelin receptor, APLNR) [ 23 ]. The ELA/APJ system is relevant to multiple biological functions, such as mesodermal differentiation, cardiogenesis, and treatment targets for heart diseases [ 24 – 26 ]. Ho et al discovered that ELA protected human embryonic stem cells against cellular stress and enhanced their self-renewal ability through PI3K/AKT pathway [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…A common modulator of both the PI3K/AKT and the NO/cGMP/PKG signalling cascades in the VSMC is Apelin [63]. Apelin stimulates the NO pathway to induce vasodilation and the PI3K/Akt pathway to induce proliferation and migration of VSMCs [64]. Due to its cardioprotective effects in the VSMC's, Apelin has been suggested as a novel therapeutic target in the cardiovascular system [64].…”
Section: Kcc In Vascular Cellsmentioning
confidence: 99%
“…Apelin stimulates the NO pathway to induce vasodilation and the PI3K/Akt pathway to induce proliferation and migration of VSMCs [64]. Due to its cardioprotective effects in the VSMC's, Apelin has been suggested as a novel therapeutic target in the cardiovascular system [64]. In 2013, researchers found that Apelin stimulated KCC activity through the NO pathway by 336% and 142% by the MAPK/PI3K pathway [65].…”
Section: Kcc In Vascular Cellsmentioning
confidence: 99%
“…A common modulator of both the PI3K/AKT and the NO/cGMP/PKG signaling cascades in the VSMCs is Apelin [ 70 ]. Apelin stimulates the NO pathway to induce vasodilation and the PI3K/Akt pathway to induce proliferation and migration of VSMCs [ 71 ]. Due to its cardioprotective effects in the VSMC’s, Apelin has been suggested as a novel therapeutic target in the cardiovascular system [ 71 ].…”
Section: Role Of Kccs In Cardiovascular Diseasementioning
confidence: 99%
“…Apelin stimulates the NO pathway to induce vasodilation and the PI3K/Akt pathway to induce proliferation and migration of VSMCs [ 71 ]. Due to its cardioprotective effects in the VSMC’s, Apelin has been suggested as a novel therapeutic target in the cardiovascular system [ 71 ]. In 2013, researchers found that Apelin stimulated KCC activity through the NO pathway by 336% and 142% by the MAPK/PI3K pathway [ 72 ].…”
Section: Role Of Kccs In Cardiovascular Diseasementioning
confidence: 99%